PENERAPAN FUNGSI-FUNGSI ADMINSTRASI PENDIDIKAN PADA PEMBELAJARAN DARING ANAK SD SELAMA COVID 19 DI DESA AIR ENAU - Ivan Riyadi; Hilian Batin; Afif Alfiyanto (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2021)
This article is written based on a unique consideration of the application of education administration. The purpose of the preparation of this study is to find out and get information regarding any obstacles faced during the online learning process of elementary school children during the Covid 19 pandemic period in Air Enau Village, Rambang Nuru District, Muara Enim Regency. This research was created using a qualitative method approach, namely the results of interviews conducted by researchers with several speakers (respondents), namely several teachers and elementary school students in Air Enau Muara Enim Village. Collection of information / data using unstructured interviews and documentation results of several learning activities in Air Enau Village. The results obtained from this study can be concluded that there are several obstacles and difficulties during the online learning process taking place experienced by teaching teachers and students and parents such as the limited communication to deliver subject matter between teachers and students, increasing expenditure costs for internet quota, The lack of understanding of the use of technology, the frequent power outages that occur which results in the loss of internet networks and lack of child awareness to remember and do their duties given by the teacher.